Journey through a tropical jungle - Forsyth, Adrian (New York : Simon and Schuster Books for Young Readers, 1988)
Presents in text and photographs some of the plants, animals, and people that live in the the tropical rain forest of Costa Rica.
Includes index.
Keywords: Rain forest ecology; Rain forests; Rain forest ecology; Rain forests; Ecology